The Chinese Diaspora and Its Identity in Southeast Asia: Research Notes from the Perspective of International Politics - WIDIATMO, DANNY; SOETJIPTO, ANI W.; YUDONO, RADEN MAISA (Issues and studies - Institute of International Relations, 2024)
Chinese identity in Southeast Asia has become complex and multifaceted over the past few decades. The Chinese diaspora in Southeast Asia has faced political challenges that pressure acculturation and assimilation, transforming its identity. This critical literature review outlines how Chinese identity in Southeast Asia has been viewed in connection with international relations and global politics. Using a taxonomic approach to scholarly works on the subject, the findings show that Chinese identity in Southeast Asia is a multi-dimensional one composed of diverse and unique community identities. Chinese identity is also viewed as a spectrum that is imagined both by nation-states and the community itself. Consequently, members of the Chinese diaspora are not simply viewed as actors, agents, or political instruments in international politics but also as independent subjects with their own stories and experiences.